Feminist ethics and social policy - DiQuinzio, Patrice, 1955-; Young, Iris Marion, 1949- (Bloomington : Indiana University Press, 1997)
Feminist Ethics and Social Policy presents complex social issues in light of a feminist ethical perspective. The spirited essays collected here critique gender blindness and biases in traditional ethical theory while developing more gender-sensitive theories and concepts. Taken together, they conceptualize issues of right action, social justice, and the human good out of the specifically gendered experience of diverse groups of women.
Taking dependency seriously: the Family and medical leave act considered in light of the social organization of dependency work and gender equality / Eva Feder Kittay -- Reconciling equality to difference : caring (f)or justice for people with disabilities / Anita Silvers -- Feminist ethics and public health care policies : a case study on the Netherlands / Selma Sevenhuijsen -- The combat exclusion and the role of women in the military / Judith Wagner DeCew -- Fathers' rights, mothers' wrongs? : reflections on unwed fathers' rights and sex equality / Mary L. Shanley --Does comparable worth have radical potential? / Carolyn H. Magid -- "Male-order" brides : immigrant women, domestic violence, and immigration law / Uma Narayan -- Intimate danger : the case for preemptive self-defense / Sharon E. Hartline -- Mixed black and white race and public policy / Naomi Zack -- Agency and alliance in public discourses about sexualities / Janet R. Jakobsen -- "Undemocratic afflictions" : a feminist response to the AIDS epidemic / Kate Mehuron -- Pornography : an uncivil liberty? / Alisa L. Carse -- Beauty and breast implantation : how candidate selection affects autonomy and informed consent / Lisa S. Parker -- Sex-selective abortion : a relational approach / Gail Weiss.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Feminist ethics; United States -- Social policy -- 1993-; Éthique féministe.; États-Unis -- Politique sociale -- 1993-; PHILOSOPHY -- Social; PHILOSOPHY -- Ethics & Moral Philosophy; Feminist ethics; Social policy; United States; Philosophy; Ethics; Philosophy & Religion; Since 1993